Metasurface circular polarizer based on rotational symmetric nanoholes. (10th May 2021) - Lv, Haoran; Mou, Zhen; Zhou, Changda; Wang, Shuyun; He, Xiaobo; Han, Zhanghua; Teng, Shuyun
Abstract: A circular polarizer is proposed based on a single layered metasurface. This metasurface circular polarizer is composed of L-shaped nanoholes etched on the silver film. The L-shaped nanoholes are rotational symmetric, and the special symmetric structure determines the polarization selection transmission of the metasurface. The theoretical analysis elaborates the design process of the metasurface circular polarizer. The proposed metasurface circular polarizers have good polarization selective transmittance, and more interestingly, they take on the opposite circular dichroism at different wavebands. The numerical simulations and experiment measurement confirm the circular dichroism of the proposed circular polarizers. The compact design, ultrathin thickness and available performance can expand the applications of the metasurface circular polarizers in the integrated optics.